IL-4 Mediated Resistance of BALB/c Mice to Visceral Leishmaniasis Is Independent of IL-4Rα Signaling via T Cells - McFarlane, Emma; Mokgethi, Thabang; Kaye, Paul M.; Hurdayal, Ramona; Brombacher, Frank; Alexander, James; Carter, Katharine C. (Frontiers in Immunology, 2019)
Previous studies infecting global IL-4R-/-, IL-4-/- and IL-13-/- mice on a BALB/c background with the visceralising parasite Leishmania donovani have shown that the T helper 2 cytokines, IL-4 and IL-13, play influential but not completely overlapping roles in controlling primary infection. Subsequently, using macrophage/neutrophil-specific IL-4R deficient BALB/c mice, we demonstrated that macrophage/neutrophil unresponsiveness to IL-4 and IL-13 did not have a detrimental effect during L. donovani infection. Here we expand on these findings and show that CD4+ T cell-(Lckcre), as well as pan T cell-(iLckcre) specific IL-4R deficient mice on a BALB/c background, unlike global IL-4R deficient mice are also not adversely affected in terms of resistance to primary infection with L. donovani. Our analysis suggested only a transient and tissue specific impact on disease course due to lack of IL4R on T cells, limited to a reduced hepatic parasite burden at day 30 post infection. Consequently, the protective role(s) demonstrated for IL-4 and IL-13 during L. donovani infection are mediated by IL-4R-responsive cell(s) other than macrophages, neutrophils and T cells.